Direct Mercury Analyzer (DMA) determination of mercury distribution in the sediments of lake Nokoué in Benin Republic-West Africa - AZON, NADIA B.N.; ADOUNKPE, GNONLONFOUN JULIEN (My University, 2021)
Mercury pollution of water bodies constitutes a hazard to both the aquatic life and the populations consuming fishery products. To anticipate the probable eco-toxicological risks that may arise from the largest lake in southern Benin, the present work aims at assessing the mercury status of the sediments of Lake Nokoué, while identifying the areas exposed to anthropogenic mercury contamination. 45 sites were sampled according to a grid plan covering the entire ecosystem of the lake. Employing a Van Veen grab, surface sediments are collected at a depth from 0 to 5 cm in three catches at each site. The composite samples formed at equal mass on the three portions were frozen, lyophilized at - 40 °C, crushed, sieved and homogenized. Fraction less than 63 µm was collected for the mercury content determination by Direct Mercury Analyzer (DMA) operating by atomic absorption according to the US EPA 7473 method. The mercury concentration varies from 1.56 µg/kg to 164.88 µg/kg with an average value of 35.18 µg per kg of sediment. The south-eastern zone of the lake is more concentrated in mercury with a summation of the mercury content of 530.3 µg/kg of sediment. However, the lake has moderate contamination overall (1 ≤ FC ≤ 3).
Keywords: Pollution; contamination; mercury; sediment; Lake Nokoué.